Issues at the Rural-Urban Fringe: Land Use Conflicts: FE549/FE549, 5/2005 - Clouser, Rodney L. (EDIS, 2005)
The purpose of this fact sheet is to discuss some of the issues that contribute to conflicts by examining both the rural and urban perspectives of the issues. Land use conflict issues at the rural-urban fringe can be grouped into three categories: (1) lifestyle issues, such as odors, noise, etc.; (2) infrastructure; and (3) property rights and wealth distribution. The issue of urban sprawl into rural areas is not a new issue in the United States and it will most likely continue for some time to come. This is EDIS document FE549, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. This document is one of a series entitled "Issues at the Rural Urban Fringe". Published May 2005.